2015
DOI: 10.1016/j.neuroimage.2015.01.053
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and neural correlates of the 5-repeat allele of the dopamine D4 receptor gene in a population lacking the 7-repeat allele

Abstract: The 5-repeat allele of a common length polymorphism in the gene that encodes the dopamine D4 receptor (DRD4) is robustly associated with the risk of attention deficit hyperactivity disorder (ADHD) and substantially exists in Asian populations, which have a lower ADHD prevalence. In this study, we investigated the effect of this allele on microstructural properties of the brain and on its functional activity during externally directed attention-demanding tasks and creative performance in the 765 Asian subjects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 99 publications
1
41
0
1
Order By: Relevance
“…It was found in course of studying aggressive and antisocial behavior that the*7R repeats were more often encountered in people convicted for violent crimes (Cherepkova et al, 2016), especially the ones, who experienced stress factors in their childhood (Schlomer et al, 2015). At the same time, it was shown for the Russian sample of inmates that the *5R allele carriers also demonstrated high aggression levels similar to those of the*7R allele carriers (Cherepkova et al, 2015), which agrees with the data on identical functional changes in the DRD4 receptor with 5 or 7 repeats (Takeuchi et al, 2015).…”
Section: Molecular-genetic Markers Of Predisposition Towards Aggressisupporting
confidence: 66%
“…It was found in course of studying aggressive and antisocial behavior that the*7R repeats were more often encountered in people convicted for violent crimes (Cherepkova et al, 2016), especially the ones, who experienced stress factors in their childhood (Schlomer et al, 2015). At the same time, it was shown for the Russian sample of inmates that the *5R allele carriers also demonstrated high aggression levels similar to those of the*7R allele carriers (Cherepkova et al, 2015), which agrees with the data on identical functional changes in the DRD4 receptor with 5 or 7 repeats (Takeuchi et al, 2015).…”
Section: Molecular-genetic Markers Of Predisposition Towards Aggressisupporting
confidence: 66%
“…Treffinger [1985] also warned that separate interpretations of TTCT subscores should be avoided. However, some studies have found specific effects of each subscale, especially originality [Takeuchi et al, 2015d]. Thus, we believe that using only the total score serves the purpose of this study.…”
Section: Divergent Thinking Assessmentmentioning
confidence: 96%
“…Thus, we believe that using only the total score serves the purpose of this study. However, some studies have found specific effects of each subscale, especially originality [Takeuchi et al, 2015d]. Thus, with the aforementioned limitation in mind, we also performed separate but identical analyses in which the total score on the S-A creativity test was replaced with each of the subscale scores.…”
Section: Divergent Thinking Assessmentmentioning
confidence: 99%
“…The following neuropsychological tests were performed according to the methods described in a previous study (Takeuchi et al 2015 fMRI Tasks fMRI was used to map brain activity during cognitive tasks. The N-back task is a typical task for fMRI studies with conditions of 0-back (simple cognitive processes) and 2-back (working memory).…”
Section: Psychological Measuresmentioning
confidence: 99%
“…The methods for MR image acquisition were described in our previous study (Takeuchi et al 2015) and reproduced below. All MRI data acquisition was performed using a 3-T Philips Achieva scanner.…”
Section: Image Acquisitionmentioning
confidence: 99%